ANALISIS PERBAIKAN KUALITAS PROSES PEMBUATAN TAHU PADA UKM TAHU JK - Tampubolon, Grace Elisabeth; Fajrah, Nofriani (LPPM Universitas Putera Batam, 2025)
JK Tofu SME still faces obstacles in meeting market demand due to wasteful activities in the production process, such as excessive soybean soaking time and inconsistent and unmeasured yeast addition. This study aims to identify factors affecting tofu production process quality and process requirement standards. The methods used are quantitative approaches through DPMO calculations, Value Stream Mapping, and QFD. The results show that the production process still has defects such as dirty, smelly, and soft tofu. Current Value Stream Mapping analysis indicates low efficiency with a PCE of 51.67% and non-value-added time (NVA and NNVA) of 290 minutes. After improvements through Future State Mapping, the PCE increased to 71.26% and the total process time decreased to 435 minutes. The average DPMO of 33,333.33 with a sigma level of 1.933 indicates that quality is still far from Six Sigma standards. Through QFD Levels 1–3, consumer needs are translated into technical specifications, product characteristics, and production process requirements. Specifications such as ingredient composition and cooking processes influence product quality, while integration across QFD levels strengthens quality control. QFD provides strategic and operational guidance for continuous product quality improvement. This study shows that analyzing the causes of waste can affect product quality and that it is necessary to determine process requirement standards.